Mucoactive agent use in adult UK Critical Care Units: a survey of health care professionals’ perception, pharmacists’ description of practice, and point prevalence of mucoactive use in invasively mechanically ventilated patients - Mark Borthwick; Danny McAuley; John Warburton; Rohan Anand; Judy Bradley; Bronwen Connolly; Bronagh Blackwood; Brenda O’Neill; Marc Chikhani; Paul Dark; Murali Shyamsundar; MICCS collaborators—Critical Care Pharmacists (PeerJ, 2020)
Background Mechanical ventilation for acute respiratory failure is one of the most common indications for admission to intensive care units (ICUs). Airway mucus clearance is impaired in these patients medication, impaired mucociliary motility, increased mucus production etc. and mucoactive agents have the potential to improve outcomes. However, studies to date have provided inconclusive results. Despite this uncertainty, mucoactives are used in adult ICUs, although the extent of use and perceptions about place in therapy are not known. Aims and Objectives We aim to describe the use of mucoactive agents in mechanically ventilated patients in UK adult critical care units. Specifically, our objectives are to describe clinicians perceptions about the use of mucoactive agents, understand the indications and anticipated benefits, and describe the prevalence and type of mucoactive agents in use. Methods We conducted three surveys. Firstly, a practitioner-level survey aimed at nurses, physiotherapists and doctors to elucidate individual practitioners perceptions about the use of mucoactive agents. Secondly, a critical care unit-level survey aimed at pharmacists to understand how these perceptions translate into practice. Thirdly, a point prevalence survey to describe the extent of prescribing and range of products in use. The practitioner-level survey was disseminated through the UK Intensive Care Society for completion by a multi-professional membership. The unit-level and point prevalence surveys were disseminated cthrough the UK Clinical Pharmacy Association for completion by pharmacists. Results The individual practitioners survey ranked ‘thick secretions’ as the main reason for commencing mucoactive agents determined using clinical assessment. The highest ranked perceived benefit for patient centred outcomes was the duration of ventilation. Of these respondents, 79% stated that further research was important and 87% expressed support for a clinical trial. The unit-level survey found that mucoactive agents were used in 83% of units. The most highly ranked indication was again ‘thick secretions’ and the most highly ranked expected patient centred clinical benefit being improved gas exchange and reduced ventilation time. Only five critical care units provided guidelines to direct the use of mucoactive agents (4%). In the point prevalence survey, 411/993 (41%) of mechanically ventilated patients received at least one mucoactive agent. The most commonly administered mucoactives were inhaled sodium chloride 0.9% (235/993, 24%), systemic carbocisteine (161/993, 16%) and inhaled hypertonic sodium cloride (127/993, 13%). Conclusions Mucoactive agents are used extensively in mechanically ventilated adult patients in UK ICUs to manage ‘thick secretions’, with a key aim to reduce the duration of ventilation. There is widespread support for clinical trials to determine the optimal use of mucoactive agent therapy in this patient population.